Business Continuity Plans - Ono, Takahiro; Ishiwatari, Mikio (World Bank, Washington, DC, 2013)
A Business Continuity Plan (BCP) identifies the potential effects of disruptions to an organization's critical operations if a disaster were to occur, and specifies effective response actions and quick recovery measures. In the Great East Japan Earthquake (GEJE), BCPs served their purpose to some extent, but certain weaknesses were identified. While BCPs helped to keep critical operational functions going, and then to rehabilitate general operations, most small-and medium-sized enterprises had, unfortunately, not even prepared BCPs. Since the private sector plays a major role in creating jobs and supporting local economies, it should be required to prepare BCPs, but with support from the government. The private sector plays a major role in creating employment and supporting the local economy, thereby ensuring regional sustainability. In the event of a disaster, the role of the private sector becomes even more important in this respect.